2015
DOI: 10.1007/s12031-015-0561-2
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Rutin in Streptozotocin-Induced Diabetic Rat Retina

Abstract: Diabetic retinopathy is widely recognized as a neurodegenerative disease of the eye. Increased oxidative stress has been considered the central factor in damaging neural retina in diabetes. Flavonoids, being powerful antioxidants, play protective roles in several oxidative stress-mediated neurodegenerative diseases. In this study, we analyzed the neuroprotective effects of a potential flavonoid, rutin, in the diabetic rat retina. Diabetes was induced in male Wistar rats by single injection of streptozotocin (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(48 citation statements)
references
References 56 publications
6
42
0
Order By: Relevance
“… HFD-STZ-induced type 2 diabetic model Niture 2014 [ 154 ] ↓ Glucose, TBARS, caspase-3 and ↑ insulin, Bcl-2 protein. STZ-induced diabetic rat retina Ola 2015 [ 156 ] Protected pancreatic beta-cell by decreasing oxidative stress. STZ induced diabetic rats Kamalakkannan and Prince 2006 [ 157 ] ↓ MDA levels and ↑ SOD and CAT.…”
Section: Flavonoids and Their Effects On Diabetesmentioning
confidence: 99%
“… HFD-STZ-induced type 2 diabetic model Niture 2014 [ 154 ] ↓ Glucose, TBARS, caspase-3 and ↑ insulin, Bcl-2 protein. STZ-induced diabetic rat retina Ola 2015 [ 156 ] Protected pancreatic beta-cell by decreasing oxidative stress. STZ induced diabetic rats Kamalakkannan and Prince 2006 [ 157 ] ↓ MDA levels and ↑ SOD and CAT.…”
Section: Flavonoids and Their Effects On Diabetesmentioning
confidence: 99%
“…MGR is a rutin-glucose conjugate, which is decomposed to rutin or quercetin by digestive enzymes in the small intestine and absorbed as quercetin in the serum [16]. In previous studies, rutin or quercetin showed neuroprotective effects on the rat retina [17,18], retinal function recovery [11,19], and ocular blood flow in animals [11,20]. In particular, quercetin improved dry eye symptoms in mice [21].…”
Section: Discussionmentioning
confidence: 99%
“…There are reports stating that these compounds confer protection against glutamate-induced apoptosis and ethanol-induced neurotoxicity in hippocampal HT22 cells by reducing caspase 3 activity [46,52]. Ola et al have reported the effectiveness of rutin in ameliorating the levels of neuroprotective factors in streptozotocin-induced diabetic rat retina as it exerts antiapoptotic activity by decreasing the levels of caspase-3 and increasing the levels of Bcl2 [53].…”
Section: Discussionmentioning
confidence: 99%